(untitled) (Revista de Diavulgación L’esprit Ingénieux, 2024)
Dear readers, Aware of your profound interest in the progress and well-being of our region, it is an honor to present you with a new issue of the L’Esprit Ingénieux journal that delves into the wonders of sustainable engineering and its impact on our environment. At a time when the urgent need to preserve our planet becomes more evident, it is essential to explore and disseminate ways in which technical innovation, especially engineering, can converge with environmental protection and social responsibility. This will shape a future that is environmentally responsible and committed to social progress. This edition of our journal provides a global view of the advancement of innovation in various engineering fields, while also emphasizing a strong social and environmental commitment. It is heartening to see that the articles align with the humanistic character of Universidad Santo Tomás. All the authors, in their writings, demonstrate a deep social and environmental commitment. In this issue of the magazine, with five research articles, we will be invited to reflect upon, learn about, and explore technical advancements in civil and environmental engineering, while being critical of the social and economic needs in Colombia.